ALTERATION BY DINITROCRESOL OF PATHWAYS FOR GLUCOSE OXIDATION IN EGGS OF ARBACIA PUNCTULATA - Keltch, A. K. (The Rockefeller University Press, 1956)
1. The C(14)O(2) production by Arbacia eggs and embryos from glucose-1-C(14), glucose-2-C(14), and glucose-6-C(14) has been measured without and with dinitrocresol in the incubation medium. In the absence of the dinitrocresol, the C(14)O(2) production from glucose-1-C(14) is more rapid than from glucose-2-C(14) and much more rapid than from glucose-6-C(14); this, together with previous findings, indicates that glucose is utilized in Arbacia eggs predominantly via the TPN shunt rather than via the aldolase step of the glycolytic pathway. In the presence of the dinitrocresol, C(14)O(2) from glucose-6-C(14) approaches that from glucose-1-C(14), indicating that, in the presence of this reagent, glucose utilization is diverted from the shunt to the glycolytic pathway. 2. Incorporation of C(14) from glucose labelled in the 1-, 2-, or 6- positions into other metabolic products of the eggs and embryos is also inhibited by dinitrocresol, particularly incorporation into the acid-insoluble fraction containing nucleoproteins.